Modification of Screen-Printed Carbon Electrode (SPCE) by Magnetic Fe3O4-Chitosan for Detection of Hexavalent Chromium - Mulyasuryani, Ani; Ponco Prananto, Yuniar (Indonesian Journal of Chemical Analysis (IJCA), 2025)
A new modification of screen-printed carbon electrode (SPCE) with magnetic Fe3O4-chitosan has been developed. Magnetic Fe3O4-chitosan was made from a mixture of Fe2+/Fe3+ (1:2) with 1% chitosan. Sodium tripolyphosphate was used as a crosslinking reagent for chitosan under alkaline conditions using NH3. SPCE modification with Fe3O4 can increase the sensitivity of Cr(VI) detection by differential pulse voltammetry (DPV). This method resulted in a sensitivity of 21.9 ppm/μA in the 0.1 - 1 ppm Cr(VI) concentration range in a 0.005 M KCl-HCl electrolyte mixture. The detection limit (LoD) is 0.2 ppm with an average accuracy of 94%.